Tailoring hollow silica spheres for enhanced hydrogen adsorption performance: Role of synthesis parameters - Saeid, Mohammed Faraj; Abdulkadir, B. A.; Herma Dina, Setiabudi (Wiley-Blackwell, 2025)
Herein, hollow silica spheres (HSS) are prepared using a sol–gel/emulsion (oil-in-water/ethanol) method where cetyltrimethylammonium bromide (CTAB) is used as a surfactant to stabilize the hydrolysis of tetraethoxysilane (TEOS) oil droplets. The adsorbents are characterized using various physicochemical characterization techniques. It is found that the hollow sphere diameters range from 250 to 400 nm, depending on the ethanol-to-water ratio (E/W), while shell thickness is tuned by CTAB concentration. The Brunauer–Emmett–Teller surface areas ranged from 816 to 1045 m2 g−1, with pore sizes around 3.1 nm according to the Barrett–Joyner–Halenda. Although silica materials show promise for hydrogen storage, their low adsorption capacity limits practical applications. Tailoring synthesis parameters, such as the ethanol-to-water ratio and CTAB concentrations, results in HSS with enhanced pore structures and surface areas, leading to improved hydrogen adsorption. The best hydrogen adsorption of 1.59 wt% is attained at an E/W ratio of 0.4 and a CTAB concentration of 5.3 mM. Post-adsorption analysis revealed a pore-filling mechanism with no structural degradation, confirming the material's stability and reversible hydrogen confinement. These results demonstrate that precise control of synthesis parameters can improve the hydrogen storage capacity of HSS materials, offering a promising strategy for efficient hydrogen adsorbents.